2000
DOI: 10.1126/science.287.5461.2274
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Progression to AIDS in HIV + Individuals with a Structural Variant of the Chemokine Receptor CX 3 CR1

Abstract: Human immunodeficiency virus (HIV) enters cells in vitro via CD4 and a coreceptor. Which of 15 known coreceptors are important in vivo is poorly defined but may be inferred from disease-modifying mutations, as for CCR5. Here two single nucleotide polymorphisms are described in Caucasians in CX3CR1, an HIV coreceptor and leukocyte chemotactic/adhesion receptor for the chemokine fractalkine. HIV-infected patients homozygous for CX3CR1-I249 M280, a variant haplotype affecting two amino acids (isoleucine-249 and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
234
10
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(260 citation statements)
references
References 34 publications
15
234
10
1
Order By: Relevance
“…Previous studies have identified genetic polymorphisms in chemokine receptor genes that encode molecules critical for HIV-1 entry into host cells (30,(33)(34)(35). Other studies have identified independent HLA associations with susceptibility or resistance to HIV-1 disease progression after infection with the virus has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified genetic polymorphisms in chemokine receptor genes that encode molecules critical for HIV-1 entry into host cells (30,(33)(34)(35). Other studies have identified independent HLA associations with susceptibility or resistance to HIV-1 disease progression after infection with the virus has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…They affect susceptibility or resistance to several infectious diseases. 45,46,[61][62][63][64] In addition, chemokine receptor signaling processes are important for leukocyte recruitment and controlled trophoblast invasion and thus for implantation and placentation. 25,26 CCR2 and CCR5 are chemokine receptors that have been assigned a function in toxoplasmosis and, independently in pregnancy, they protect from uncontrolled T. gondii replication in adults and favor trophoblast survival or invasion (related to a Th1 response), partially explaining the first-trimester resistance against vertical transmission.…”
Section: Immune Response In Acquired Toxoplasmosismentioning
confidence: 99%
“…19 Real-time detection and analyses were performed on an ABI 7700 thermocycler (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…We identified two common single-nucleotide polymorphisms (SNPs), known as V249I and T280M, in the open reading frame of the chemokine receptor CX3CR1 gene. 19 The common CX3CR1-I249 allele and its genetically linked partner, the CX3CR1-M280 allele, are associated with a reduced risk of cardiovascular diseases 20,21 and inflammatory lung disorders. 22,23 CX3CR1 is thus another plausible link between inflammation, airway remodelling and asthma.…”
Section: Introductionmentioning
confidence: 99%